2016
DOI: 10.1111/add.13491
|View full text |Cite
|
Sign up to set email alerts
|

Non-medical use of prescription opioids is associated with heroin initiation among US veterans: a prospective cohort study

Abstract: Aims To estimate the influence of non-medical use of prescription opioids (NMUPO) on heroin initiation among U.S. veterans receiving medical care. Design Using a multivariable Cox regression model, we analyzed data from a prospective, multi-site, observational study of HIV-positive and an age/race/site matched control group of HIV-negative veterans in care in the United States. Approximately annual behavioral assessments were conducted and contained self-reported measures of NMUPO and heroin use. Setting V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 51 publications
2
56
2
1
Order By: Relevance
“…Specifically, our findings are consistent with a growing body of research suggesting that while increased regulation of prescription opiates can reduce the likelihood of these substances to be present in overdoses, [29][30][31] it also results in nonmedical prescription opiate users-those using prescription opiates, without a prescription, for the purposes of experiencing or feeling the effects of the drug-turning to illicit opioids. [32][33][34][35] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, our findings are consistent with a growing body of research suggesting that while increased regulation of prescription opiates can reduce the likelihood of these substances to be present in overdoses, [29][30][31] it also results in nonmedical prescription opiate users-those using prescription opiates, without a prescription, for the purposes of experiencing or feeling the effects of the drug-turning to illicit opioids. [32][33][34][35] …”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] The dramatic increase in prescription opiates during the 1990s and 2000s is well documented and is generally attributed to greater social acceptance, diversification in what these drugs are used for, and marketing activities of pharmaceutical companies. 36,37 Our Table 3 shows the decline in prescriptions for codeine and oxymorphone is evident as of 2012 whereas the decline in prescriptions for all other opioids is not present until 2013.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…We read with interest the article by Banerjee and colleagues [1], entitled 'Non-medical use of prescription opioids is associated with heroin initiation among US veterans: a prospective cohort study', published in Addiction. The authors aimed to estimate the influence of non-medical use of prescription opioids (NMUPO) on heroin initiation among US veterans.…”
mentioning
confidence: 99%
“…They found that non-medical use of prescription opioids (NMUPO) was associated positively and independently with heroin initiation. Banerjee et al conclude that new-onset NMUPO is a strong risk factor for heroin initiation among HIV-infected and uninfected veterans in the United States [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation